Role of Metformin and AKT Axis Modulation in the Reversion of Hypoxia Induced TMZ-Resistance in Glioma Cells - Lo Dico, Alessia; Valtorta, Silvia; Ottobrini, Luisa; Moresco, Rosa Maria (Frontiers in Oncology, 2019)
Hypoxia is a key driver of tumor adaptation being involved in tumor progression as well in resistance to therapy. Hypoxia-dependent factors could be attractive therapeutic targets in GBM management, that up to date is characterized by a poor prognosis. Several molecular mechanisms have been investigated to explain the anti-cancer effects of MET in GBM. Here, we found that MET, in combination with TMZ standard therapy, could improve the chemo-sensitivity and overall could revert the chemoresistance also in hypoxic condition. COMBO was indeed able to induce a "sensitive-like" pattern of the apoptotic genes in TMZ-resistant cells, reducing cell viability. Moreover, we assessed HIF-1 modulation and the potential role exerted by PI3k/AKT pathway. In U251, COMBO produced a marked decrease of stem cell markers, HIF-1α levels and AKT activation inducing a pro-apoptotic phenotype. In T98 cells, COMBO failed to reduce the hypoxia-dependent increase in CD133 positive cells. The administration of the dual PI3K/mTOR inhibitor BEZ235 potentiated the effect of COMBO on cell viability during hypoxic conditions suggesting the block of the PI3k/AKT pathway as a complementary target to further overcome GBM resistance.